Addressing the Unaddressed: Changemakers’ Hopes for the Future around Issues of Sexuality in Catholic Higher Education - Theological Insights - Levand, Mark A. (The journal of religion & society, 2021)
Issues of sexuality in Catholic higher education often go unaddressed, under examined, or handled with inadequate care. In a larger study of the experience of 31 changemakers at 17 different Catholic colleges and universities, participants discussed how they effected change around an issue of sexuality at their university. At the end of the interviews, participants were asked about what hopes they had for the future of sexuality in Catholic higher education. This article is an exploration of the emergent themes in their answers to future hopes, as well as insights and support from the Catholic theological tradition.